FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI AKADEMIK PADA REMAJA - , Drs. I Made Rustika, M.Si.; , Prof. Dr. Endang Ekowarni ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A question that often emerged on adolescent academic performance is: âwhy some adolescents have remarkable academic performance while some others could only dream of it?â. The social cognitive theory believes that academic performance is strongly influenced by the environmental stimulus and the internal process of the learner. In this research, the external factor that was considered research variable was the authoritative parenting style, while the internal factors that were considered research variables were: g factor of intelligence, self-efficacy, and emotional intelligence. The connection of these five variables was arranged into a theoretical model. The subjects of the research were the second-semester-students of the Faculty of Medicine, Udayana University, Denpasar. The instruments used in this research were: The APM (Advanced Progressive Matrices) Intelligence Test